Assessment of Quality of Obturation, Instrumentation Time and Intensity of Pain with Pediatric Rotary File (Kedo-S) in Primary Anterior Teeth: A Randomized Controlled Clinical Trial - Govindaraju, Lavanya (Int J Clin Pediatr Dent, 2018)
AIM: The purpose of this study was to clinically compare and evaluate the efficiency of pediatric rotary file kedo-S with hand K files and ProTaper rotary files during root canal preparation of primary anterior teeth. MATERIALS AND METHODS: Forty-five children requiring pulpectomy in any one of the vital primary anterior teeth were included. The children were randomly assigned to one of the three groups (15 per group), where the instrumentation was done using hand files in group 1, ProTaper rotary files in group 2 and Kedo-S rotary files in group 3. The instrumentation time, pain perception and the quality of obturation was assessed, and the statistical analysis was done using statistical package for social sciences (SPSS) software. RESULTS: Statistically decreased instrumentation time was observed with the use of Kedo-S rotary file system (p < 0.05) when compared to the other two file systems. The intensity of pain experienced during instrumentation was also lesser with Kedo-S rotary file (p < 0.05). No significant difference was noted in the obturation quality with the exclusive pediatric rotary file when compared with the other two groups (p > 0.05). CONCLUSION: Kedo-S rotary files decrease the instrumentation time and intensity of the pain perception during canal instrumentation which positively influences the cooperation of the children. CLINICAL SIGNIFICANCE: Use of exclusive pediatric rotary files (Kedo-S) for root canal preparation in primary teeth reduces the fatigue of both the children and the dentists. Also, influences the behavior of the children in a more positive way thereby instilling a positive dental attitude. HOW TO CITE THIS ARTICLE: Govindaraju L, Jeevanandan G, Subramanian EMG, Vishawanathaiah S. Assessment of Quality of Obturation, Instrumentation Time and Intensity of Pain with Pediatric Rotary File (Kedo-S) in Primary Anterior Teeth: A Randomized Controlled Clinical Trial. Int J Clin Pediatr Dent, 2018;11(6):462-467.